The Silos of Natural Resource Governance: Implications of Sector-led Coastal Management at the Village Level in Kenya and Zanzibar-Tanzania - Fiona Nunan; Marlyn A Omondi; Aziza Y Nchimbi; Mwita M Mangora; James G Kairo; Mwanahija S Shalli; Narriman S Jiddawi (Conservation & Society, 2020)
Taking a coordinated, holistic approach to the governance of coastal ecosystems is widely advocated in recognition of the need to manage ecosystems as a whole. Despite commitment to approaches such as integrated coastal zone management and ecosystem-based management of fisheries, governance remains fragmented, with sectors such as environment, fisheries and forestry maintaining separate systems of governance from the national to village level. These systems include the formation of separate community-based structures, reporting directly to the respective sectoral ministry. This raises questions about how this collaborative governance approach aligns with taking a more integrated, holistic approach to management. The paper draws on findings from research in Kenya and Zanzibar-Tanzania in coastal villages where forest and fisheries management groups have been formed. The research found that the groups operate in compartmentalised ‘silos', in contrast to the interrelated ecosystems on which they depend, with little coordination of plans and priorities. In addition, these groups are not consistent in their relationship to local government, answering directly to the sectoral ministry rather than democratic local government, raising issues for accountability and sustainability. These dual challenges of a sectoral-focus and long-term sustainability must be addressed for management of ecosystems to be integrated and effective.